2019
DOI: 10.3390/cells8060616
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Circular RNA circ-FoxO3 Inhibits Myoblast Cells Differentiation

Abstract: CircRNA is a type of closed circular non-coding RNA formed by reverse splicing and plays an important role in regulating the growth and development of plants and animals. To investigate the function of circ-FoxO3 in mouse myoblast cells’ (C2C12) differentiation and proliferation, we used RT-qPCR to detect the expression level of circ-FoxO3 in mouse myoblast cells at different densities and different differentiation stages, and the specific interference fragment was used to inhibit the expression level of circ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…It is not clear whether the previously reported circular FOXO3 transcripts have the same structure as the one we have identified, since previous studies do not give its exon structure. A circRNA from the FOXO3 gene identical to the one we have identified has also previously been demonstrated to inhibit myoblast differentiation in mouse cells (Li et al 2019). Genetic variation in the FOXO3 gene itself has previously been associated with extreme longevity (Flachsbart et al 2017;Fuku et al 2016) and has also been associated with maintenance of telomere length (Davy et al 2018).…”
Section: Discussionmentioning
confidence: 53%
“…It is not clear whether the previously reported circular FOXO3 transcripts have the same structure as the one we have identified, since previous studies do not give its exon structure. A circRNA from the FOXO3 gene identical to the one we have identified has also previously been demonstrated to inhibit myoblast differentiation in mouse cells (Li et al 2019). Genetic variation in the FOXO3 gene itself has previously been associated with extreme longevity (Flachsbart et al 2017;Fuku et al 2016) and has also been associated with maintenance of telomere length (Davy et al 2018).…”
Section: Discussionmentioning
confidence: 53%
“…MSTN belongs to the TGF-β superfamily and can negatively control muscle growth. Our laboratory has contributed to develop a safe and effective strategy to enhance animal growth and meat production for a long time [ 11 , 12 , 24 ]. Various studies have shown that inhibiting MSTN activity can effectively promote the growth of animal muscles [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle satellite cells (SMSCs), it subsequently activates myogenesis through sponging miR-7 [70,71]. Several circRNAs also work in the same way by sponging miRNAs to promote or repress the myogenic differentiation of MSCs, such as circHIPK3 and circ-FoxO3 [72][73][74]. Other than that, cir-cRNAs have been identified to be differentially expressed in different differentiation stages of neural stem cells (NSCs).…”
Section: Myogenesis and Neuronalmentioning
confidence: 99%